Twilight of atheism the rise and fall of disbelief in the modern world - McGrath, Alister Edgar, 1953- (London, UK Rider, 2004)
Includes bibliographical references and index.
electronic resource : http://www.loc.gov/catdir/description/random044/2003055531.html
Keywords: Atheism -- history, 21st century